2020
DOI: 10.1007/s12253-020-00855-7
|View full text |Cite
|
Sign up to set email alerts
|

Architectural Grade Combined With Spread Through Air Spaces (STAS) Predicts Recurrence and is Suitable for Stratifying Patients Who Might Be Eligible for Lung Sparing Surgery for Stage I Adenocarcinomas

Abstract: The spread through air spaces (STAS) has a main role in local recurrence of stage I lung adenocarcinomas (LAs), therefore its presence might question sublobar resection as a therapeutic option. The aim of our study was to evaluate the distribution of STAS in stage I LAs, to stratify patients according to local recurrence and to identify a group of patients who might be suitable for sublobar surgery. Patients resected with LA were included. The presence of STAS was recorded on hematoxylin eosin stained slides a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 37 publications
1
10
1
Order By: Relevance
“…Shiono and Yanagawa [ 23 ] have investigated 318 patients with stage I lung adenocarcinomas and found that male gender, smoking, solid nodules, stage IB, lymphovascular and pleural invasion were associated with the STAS1. Similarly, in a previous study, we found that the STAS1 is an independent adverse prognostic factor in lobectomy specimens [ 15 ].…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Shiono and Yanagawa [ 23 ] have investigated 318 patients with stage I lung adenocarcinomas and found that male gender, smoking, solid nodules, stage IB, lymphovascular and pleural invasion were associated with the STAS1. Similarly, in a previous study, we found that the STAS1 is an independent adverse prognostic factor in lobectomy specimens [ 15 ].…”
Section: Discussionsupporting
confidence: 82%
“…The ex vivo artefacts (shown in Fig. 2c ) defined in our previous publication were excluded from evaluation [ 15 ]. All patients underwent follow-up that consisted of regular physical examination, chest X-ray, abdominal ultrasonography, and chest computer tomography.…”
Section: Methodsmentioning
confidence: 99%
“…The 2021 WHO Classification of Thoracic Tumours pointed out that STAS is a histologic feature of prognostic significance [8]. Among them, STAS is an important risk factor for tumor recurrence after surgery for stage I NSCLC [9][10][11]. However, the existence of STAS has also been questioned by many scholars, who believe that STAS may be an artifact of human manipulation due to spreading caused by knife cuts during specimen processing [12], although some studies have been conducted on the specimen retrieval process and confirmed that STAS is an in vivo phenomenon that exists preoperatively and is not a result of spreading caused by specimen processing [13].…”
Section: Introductionmentioning
confidence: 99%
“…28 STAS can be identified in both paraffin tissue and frozen sections. 29 As a powerful indicator for identifying high-risk patients, STAS has been employed by several grading systems, including those proposed by Kadota et al and Sica et al 7 In addition, our model employs a quantitative cutoff of 10% for the selected variable. This cutoff is utilized to evaluate the solid subtype, which is more straightforward to recognize than the high-grade structures containing micropapillary, cribriform, or complex glandular patterns.…”
Section: Discussionmentioning
confidence: 99%